Factores psicológicos que inciden en la decisión de compra de zapatos y su intención de compra en adultos jóvenes universitarios - Bautista Bejarano, María Lucía (Universidad Antonio Nariño, 2023)
This research describes the response of the psychological factors that affect the decision to purchase shoes, establishing the relevant factors associated with the purchase decision, identifying them as a purchase process going through relevant phases such as recognition of the need, information search, evaluation of alternatives, purchase decision and postpurchase behavior.